Assessing the management effectiveness of China's marine protected areas: Challenges and recommendations. (1st June 2022) - Zeng, Xu; Chen, Mingyang; Zeng, Cong; Cheng, Shuo; Wang, Zihan; Liu, Shurong; Zou, Chengxuan; Ye, Shufeng; Zhu, Zhengguang; Cao, Ling
Abstract: Rapid population growth is putting enormous pressure on fragile marine ecosystems. Marine protected areas (MPAs) are a widely adopted management tool to address these challenges, but their conservation effectiveness is uncertain, especially in developing countries such as China. Management effectiveness evaluation (MEE) is an efficient method for assessing MPA outcomes and identifying key impact factors. However, only a limited number of MEEs have been conducted for China's MPAs in the past two decades, thus largely limiting their improvement of management. In this context, we conducted a comprehensive review of MPAs status and existing MEEs in China. We found that despite the significant increase in the number and coverage of China's MPAs, their conservation effectiveness might be impacted by the lack of systematic planning, adequate funding, appropriate zoning, long-term monitoring, and sound laws. Major challenges to the evaluation of MPA management effectiveness in China include the lack of a standardized framework, limited survey data, financial support, and public engagement. To address these challenges, we developed a comprehensive framework based on the common objectives of China's MPAs and existing MEE frameworks. We also recommend based on the developed framework: 1) establishing long-term monitoring pilots in national MPAs; 2) providing sustained funding support for MEE, monitoring and capacity building from government, social capital, and ecotourism; and 3) promoting public participation in MPA management and evaluation through advocacy, incentive mechanisms, and establishment of committees. Adopting our recommendations can strengthen adaptive management and provide new insights into evidence-based decision-making for MPAs in China. Graphical abstract: Image 1 Highlights: A comprehensive review of China's MPAs and their management effectiveness evaluations (MEEs) is conducted. The effectiveness of China's MPAs urgently needs to be improved through adaptive management. The lack of a standardized framework, survey data, financial support, and public engagement hinder the MEEs forChina's MPAs. A comprehensive and standardized framework was proposed for China's MPAs.